2019
DOI: 10.1364/oe.27.029460
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the evanescent Kerr effect in optical nanofibers

Abstract: Optical nanofibers have recently emerged as attractive nanophotonic platforms for many applications ranging from quantum technologies to nonlinear optics, due to both their tight optical confinement and their wide evanescent field. Herein we examine both theoretically and experimentally the optical Kerr effect induced by the evanescent field of a silica nanofiber surrounded by different nonlinear liquids such as water, ethanol and acetone and we further compare them with air cladding. Our results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The acoustic wavevector matches the wave vectors difference between the two cross-polarized optical modes supported by the birefringent fibers [9][10]. Since backward Brillouin scattering in ONFs features both longitudinal L0m and torso-radial TR21 modes, we may expect similar effects in a slightly birefringent nanofiber [4].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The acoustic wavevector matches the wave vectors difference between the two cross-polarized optical modes supported by the birefringent fibers [9][10]. Since backward Brillouin scattering in ONFs features both longitudinal L0m and torso-radial TR21 modes, we may expect similar effects in a slightly birefringent nanofiber [4].…”
Section: Introductionmentioning
confidence: 70%
“…Silica optical nanofibers (ONF) are very attractive nanophotonic platforms for many applications such as optical sensing and nonlinear photonics due to both their wide evanescent field and the tight field confinement in the waist region [1][2][3][4]. It has been further shown that ONFs possess unique elastic properties owing to the strong coupling between shear and longitudinal acoustic waves [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the sub-nanosecond regime, as the effective length of interaction and the pump length are of the same magnitude ( ~ 10 𝑐𝑚), backward nonlinear effects can be favored [13]. On OSA2, we observed backward Raman scattering, neither in silica nor in ethanol.…”
Section: Nonlinear Characterization Of the Convertermentioning
confidence: 78%
“…This property has been exploited for optical sensing [2] or optical traps for quantum applications [3]. The excitation of optical nonlinearities such as Stimulated Raman Scattering (SRS) [4] or Kerr effect in the evanescent field of nanofibers immersed in liquids has also been demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%